The Study of Best Management Practices in Sri Lanka's High Performing Companies - Nanayakkara, Gunapala (Journal of Comparative International Management)

(untitled) (Management Futures, 1999)
From a methodological point of view, the study of best management practices provides an interesting inductive method for those who wish to get closer to the art and science of managerial practice. In a sectoral sample of 40 large and successful companies in Sri Lanka, a group of researchers surveyed the current management practices and how they contributed to company performance. This paper summarizes the conceptual, methodological and operational aspects of the study on the five best management practices.